The Validity of Theoretical Model of Rhetorical Sensitivity Based on Communication Mentality Structure in Multiethnic Context: Study for Certified Teachers in District of Simalungun, North Sumatera - Purba, Priza Audermando (JURNAL KOMUNIKASI INDONESIA, 2017)
The main aim of this research is to asses how fit the theoretical model of rhetorical sensitivity based on communication mentality structure when tested to the professional whose their activities are highly controlled by Law and ethnic expectations. Model research is an integration of four rhetorical sensitivity theories. All variables are measured at interval levels and being deduced in self-report format with 7 points Likert-Type Scale. Samples are 339 certified teachers that are selected by systematic random sampling technique with margin of error 4%. Research is designed as a cross-sectional survey. By using structural equation modeling (SEM) method, this research found that there are three of six absolute fit measures were classified good fit. All incremental fit measures were classified good fit. All parsimonious fit measures were apparently classified good fit. There 45 0f 47 indicators were valid and reliable. Twelve of fifteen casual paths were significance. Generally, this research concluded that not all data that are taken from certified teachers in multiethnic context fit to the theoretical model. Tujuan utama penelitian ini adalah untuk menilai seberapa sesuai model teoritis kepekaan retoris berdasarkan struktur mental komunikasi saat diuji kepada profesional yang kegiatannya sangat dikuasai oleh harapan hukum dan etnis. Model penelitian adalah integrasi dari empat teori kepekaan retoris. Semua variabel diukur pada skala interval dan menggunakan format 7 poin Skala Likert. Sampel adalah 339 guru bersertifikat yang dipilih dengan teknik sampling acak sistematis dengan margin error ± 4%. Penelitian dirancang sebagai survei cross-sectional. Dengan menggunakan metode pemodelan persamaan struktural (SEM), penelitian ini menemukan bahwa ada tiga dari enam ukuran kecocokan absolut yang diklasifikasikan sesuai. Semua ukuran inkramental diklasifikasikan sesuai. Semua ukuran parsimoni diklasifikasikan sesuai. Dari 47 indikator yang dipakai, sebanyak 45 indikator valid dan reliabel. Sebanyak dua belas dari lima belas jalur hubungan antar variabel terbukti signifikan. Secara umum, penelitian ini menyimpulkan bahwa tidak semua data yang diambil dari guru bersertifikasi dalam konteks multietnis sesuai dengan model teoritis kepekaan retoris.